PERBANDINGAN SIKLUS HIDUP PRODUK DOTA 2 DAN CS:GO BERDASARKAN STRATEGI EVENT MARKETING - Junianta, Reynaldi Dwi; Sanaji, Sanaji (Fakultas Ekonomi, Universitas Negeri Jakarta, 2019)
The purpose of this research is to get the Product Life Cycle’s phase from Dota 2 and CS:GO based on Polli and Cook model and to know the difference of impact of Marketing Event Dota 2 and CS:GO strategy on Product Life Cycle Dota 2 and CS:GO. The method of this research is qualitative. The data used are secondary data collected through documents on the internet. The data processed by the Polli and Cook formulas to produce the Product Life Cycle stages and data on Event Marketing both games are collected and compared each criteria. The results show that product life cycle both online games can be proved by Polli and Cook model. At each stage the two games have different strategies. Dota 2 Product Life Cycle stages are: 1) the introduction phase starts and ends in July 2012; 2) the growth stage starts in July 2012 and ends in November 2012; 3) the maturity phase starts in December 2012 until now. CS:GO Product Life Cycle stages are: 1) introduction phase starts and ends in August 2012; 2) the growth stage starts in August 2012 and ends in January 2014; 3) the maturity stage starts in February 2014 until now.